Pengenalan Investasi dan Asuransi sebagai Strategi Penguatan Literasi Keuangan : (Penyuluhan Ibu PKK Dusun Sidawung, Kendal) - Lathifatul Aulia; Arista Fitri Diana; Zakaria Bani Ikhtiyar; Wulan Bhakti Pertiwi; Nova Putri Ardelia; Qurota A’yun; Tarita Intan Soraya (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The dynamic development of socio-economic conditions, accompanied by increasing household needs and income uncertainty, requires communities to possess sound and sustainable financial management capabilities. Women, particularly housewives and micro-enterprise actors, play a strategic role in managing household and business finances. However, limited understanding of financial planning, investment, and insurance remains a major challenge that may increase vulnerability to financial risks. One strategic measure to strengthen household economic resilience is the enhancement of financial literacy through targeted and contextual education, especially regarding the introduction of investment and insurance as instruments for financial planning and risk protection. This community service program aims to improve women’s financial literacy through educational activities focusing on the basic principles of investment and insurance, as well as their application in the context of entrepreneurship and household financial management. The target participants are members of the PKK Women’s Group in Sidawung Hamlet, Kali Gading Village, Boja Subdistrict, Kendal Regency. The implementation methods include interactive lectures, simple demonstrations, discussions based on local case studies, and evaluation through pre–post tests. Indicators of program success include improvements in participants’ financial literacy scores, enhanced understanding of investment and insurance concepts, and increased motivation to adopt regular saving habits, maintain business financial records, and consider appropriate simple investment instruments and insurance products. The expected outcomes of this program are improved basic financial literacy knowledge and skills, as well as the development of follow-up action plans by the PKK group related to financial management and risk protection for family-based enterprises.